Comparing tissue oximetry to doppler monitoring in 1367 consecutive breast free flaps. Issue 1 (3rd March 2022) - Johnson, Braden M.; Cullom, Melissa E.; Egan, Katie G.; Nazir, Niaman; Elver, Ashlie A.; Limpiado, MarcArthur J.; Lai, Eric C.; Butterworth, James A.
Abstract: Background: Retrospective studies evaluating tissue oximetry in a more recent cohort have shown superiority in flap outcomes. This study compares the use of tissue oximetry in a historical cohort to clinical observation and handheld doppler in a more recent cohort. We hypothesize that there is no benefit to using tissue oximetry. Methods: A retrospective review was performed on patients who underwent abdominal‐based autologous breast reconstruction by five microsurgeons at an academic institution from 2009 to 2020. Method of postoperative flap monitoring was determined then operative details and complications were analyzed. Results: 1367 flaps were reviewed; 740 flaps in 460 patients were monitored with clinical observation and tissue oximetry, and 627 flaps in 391 patients were monitored with clinical observation and handheld doppler. There were no statistical differences in ischemic ( p = .59) or congestive complications ( p = .41), flap salvage rates when exploring for venous or arterial compromise ( p = .52), or early flap loss ( p = .56). Although not significant, acute flap‐related return to the operating room was lower in the doppler group (4.6%) compared to the oximetry group (6.1%; p = .22). Flaps monitored with tissue oximetry had a statistical increase in length of stay (4.8 ± 1.4 days vs. 3.8 ± 1.6 days; p ≤ .001). The rates of late partial flap loss and fat necrosis were significantly higher in the oximetry group (2.6%, 19/740 vs. 0.3%, 2/740; p = .04) and (18.2%, 135/740 vs. 13.6%, 85/627; p = .02), respectively. Conclusions: There is no statistical benefit to the use of tissue oximetry compared to handheld doppler in flap monitoring with regards to flap outcomes.